Case report: High-dose epoprostenol therapy in pediatric patients with pulmonary hypertension and developmental lung disease - Fukasawa, Yoshie; Yamamoto, Hidenori; Ito, Miharu; Saito, Akiko; Go, Kiyotaka; Morimoto, Yoshihito; Yasuda, Kazushi; Sato, Yoshiaki; Hayakawa, Masahiro; Kato, Taichi (Frontiers in Pediatrics, 2023)
Pulmonary hypertension (PH) with developmental lung disease is a life-threatening disease and accounts for 10-12% of pediatric PH patients. Administration of specific pulmonary vasodilators to pediatric PH patients has brought about improvement of their long-term prognosis. Intravenous epoprostenol therapy is a gold standard therapy for severe idiopathic pulmonary arterial hypertension (IPAH), but there are few reports demonstrating the efficacy of epoprostenol for pediatric PH patients with developmental lung disease, especially when treating with high doses of epoprostenol. Two cases of pediatric PH patients with alveolar capillary dysplasia with misalignment of pulmonary veins (ACD/MPV) and congenital diaphragmatic hernia (CDH) with bronchopulmonary dysplasia (BPD), respectively, treated with epoprostenol above 100 ng/kg/min are presented. In these two cases, severe PH was improved significantly by an aggressive increase of the epoprostenol infusion rate with administration of oral pulmonary vasodilators and appropriate respiratory management, without any significant adverse effects. High-dose epoprostenol therapy may be one of the therapeutic options in pediatric PH patients with developmental lung disease.